GE_GERICHTE P/14250/2011 vom 14. Januar 2014 - GE Cour de justice (2014)
INTENTION; DOL ÉVENTUEL; INFRACTIONS CONTRE LE PATRIMOINE; BRIGANDAGE; FIXATION DE LA PEINE | CP.140.3; CP.140.4; CP.48.D; CP.47